Students’ entrepreneurship development improvement tendencies in Lithuania - Župerka, Aurimas (Business, Management and Economics Engineering, 2010)
Main students’ characteristics, necessary in order to become a successful entrepreneur, are presented in the theory of enterprise. The analysis, helping to realize how the educators understand the concept of entrepreneurship, is carried out. The evaluation of entrepreneurship development integration into other le-arning subjects is carried out as well. Entrepreneurship development methods used in the enterprise development program are identified in the article. A study covers the problems, which educators of educational institutions face while developing the entrepreneurship of the students. While summarizing the analysis of the study, the development tendencies of students’ entrepreneurship in Lithuanian schools are presented in the article. Article in Lithuanian. Moksleivių verslumo ugdymo tobulinimo kryptys Lietuvoje